2020
DOI: 10.5713/ajas.18.0604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fat and protein levels in calf ration on performance of Sahiwal calves

Abstract: The current study was carried out to examine the response of different levels of fat and protein in calf starter on nutrient utilisation, nitrogen metabolism, weight gain, blood parameters, and immunity level in pre-ruminant calves. Methods: Twenty four calves (5 days old) were divided into six groups in a 2×3 factorial design, with two levels of fat (10% and 14%) and three levels of protein (18%, 21%, and 24%). The calves were kept in individual pens for 120 days and fed with whole milk (1/10th of body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…In accordance with the present results, Daneshvar et al (2016) and Makizadeh et al (2020) reported no significant change in TP after feeding calves with different levels of CP; furthermore, both results showed no significant effect on ALB concentration. In contrast to our results, Sharma et al (2019) found that TP concentration increased with higher levels of protein in the starter, but no significant change was observed in ALB. Blood urea N (BUN) concentration is generally considered an indicator of protein status (Kohn et al, 2005).…”
Section: Blood Indexcontrasting
confidence: 99%
“…In accordance with the present results, Daneshvar et al (2016) and Makizadeh et al (2020) reported no significant change in TP after feeding calves with different levels of CP; furthermore, both results showed no significant effect on ALB concentration. In contrast to our results, Sharma et al (2019) found that TP concentration increased with higher levels of protein in the starter, but no significant change was observed in ALB. Blood urea N (BUN) concentration is generally considered an indicator of protein status (Kohn et al, 2005).…”
Section: Blood Indexcontrasting
confidence: 99%
“…The results revealed that the milk conversion ratio was larger for A2-calves compared to A1-calves (10.5 and 9.2, respectively). In this context, Sharma et al recently reported that feed conversion efficiency was significantly improved with higher protein level [ 41 ]. Additionally, the authors indicated that the nutrient digestibility increased with an increasing protein level.…”
Section: Resultsmentioning
confidence: 99%
“…The fact is in agreement with the ndings of Litherland et al (2014) and Hill et al (2009) who reported a reduced feed intake in calves while fed a diet with higher fat content. Increased fat content could increase the calf starter's energy density and ful lled the potential energy requirement earlier (Sharma et al 2020). The identical DMI of MOC, SM, and MOCSM groups might be due to similar concentrations of fat and protein.…”
Section: Discussionmentioning
confidence: 99%